2002
DOI: 10.1088/0957-4484/13/2/319
|View full text |Cite
|
Sign up to set email alerts
|

A technique for fabricating InGaAs/GaAs nanotubes of precisely controlled lengths

Abstract: Single-crystal nanotubes of controlled lengths were produced on sidewalls of V-grooves and on a cleaved facet of a heterostructure. This was done using selective molecular-beam-epitaxy growth of a strained InGaAs/GaAs strip and subsequent self-rolling of this strip in a tube. The proposed technique is capable of ensuring good reproducibility for all sizes and exact positioning of nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 7 publications
(8 reference statements)
0
20
0
Order By: Relevance
“…An in-depth characterization of local strain distribution in RUNTs is required to understand the growth process and to optimize the resulting mechanical and electronic properties toward technological applications such as band-gap engineering for optoelectronic devices (Lamberti, 1996a(Lamberti, , 1996b. It was demonstrated, combining micro-Raman Songmuang et al, 2006) and TEM (Prinz et al, 2002;Songmuang et al, 2006), that RUNTs are formed by an alternation of crystalline and noncrystalline layers representing a radial superlattice . Nevertheless, a nondestructive structural characterization of superlattice interfaces, without removal of the RUNTs from the substrate, required the use of XRD (Pietsch, Holý, and Baumbach, 2004).…”
Section: Iii-v Semiconductorsmentioning
confidence: 99%
“…An in-depth characterization of local strain distribution in RUNTs is required to understand the growth process and to optimize the resulting mechanical and electronic properties toward technological applications such as band-gap engineering for optoelectronic devices (Lamberti, 1996a(Lamberti, , 1996b. It was demonstrated, combining micro-Raman Songmuang et al, 2006) and TEM (Prinz et al, 2002;Songmuang et al, 2006), that RUNTs are formed by an alternation of crystalline and noncrystalline layers representing a radial superlattice . Nevertheless, a nondestructive structural characterization of superlattice interfaces, without removal of the RUNTs from the substrate, required the use of XRD (Pietsch, Holý, and Baumbach, 2004).…”
Section: Iii-v Semiconductorsmentioning
confidence: 99%
“…However, the zinc blend four fold symmetry does not appear to be affected by the rolling action [17,23,63]. Stacking faults were found in some nanotubes where the rolling involves a misorientation [40]. TEM has also been done on In x Ga 1−x As/GaAs tubes functionalized with a self-assembled monolayer (SAM) of 1-hexadecanethiol, which created a multiperiod inorganic/organic radial superlattice when rolled up with multiple turns [23].…”
Section: Structural Properties By Transmission Electron Microscopy (Tmentioning
confidence: 99%
“…Insight into the crystalline structure of RUNTs was previously gained by transmission electron microscopy [12,[16][17][18] and micro-Raman spectroscopy [12,16]. TEM revealed that the rolled-up nanotubes can consist of radial superlattices with alternating crystalline and noncrystalline layers [12].…”
mentioning
confidence: 99%